2019
DOI: 10.1111/jpy.12856
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Chlorella vulgaris culture for waste treatment from anaerobic biomass biodigestion at the Piaszczyna (Poland) integrated facility

Abstract: Many strains of microalgae are potentially useful for industrial purposes. Microalgal biomass and microalgae‐derived substances are becoming valuable products with a widening range of applications including biofuels and human food. In this study, the possibility of using the methane waste from biomass biodigestion in the cultivation of Chlorella vulgaris biomass with simultaneous waste treatment was investigated. The methane waste from biomass biodigestion was obtained from a multifunctional facility (Piaszczy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Alburquerque et al [11], Jasiulewicz and Janiszewska [12], and Łagocka et al [13] indicated that, given the environmental risks and benefits, the use of this waste in agriculture is most rational, provided that methods for its use are developed. The limitation of environmentally harmful synthetic fertilization by the use of biogas plant waste seems to be very important, as has been similarly demonstrated in the case of microalgae and water plants from the family Lemnaceae, which applied to medium enabled a reduction of the recommended artificial fertilizer doses [14][15][16][17]. The use of waste from biogas plants for fertilizing purposes is part of the strategy of the circulating production of energy plants in which waste becomes a raw material in the next crop cycle.…”
Section: Introductionmentioning
confidence: 96%
“…Alburquerque et al [11], Jasiulewicz and Janiszewska [12], and Łagocka et al [13] indicated that, given the environmental risks and benefits, the use of this waste in agriculture is most rational, provided that methods for its use are developed. The limitation of environmentally harmful synthetic fertilization by the use of biogas plant waste seems to be very important, as has been similarly demonstrated in the case of microalgae and water plants from the family Lemnaceae, which applied to medium enabled a reduction of the recommended artificial fertilizer doses [14][15][16][17]. The use of waste from biogas plants for fertilizing purposes is part of the strategy of the circulating production of energy plants in which waste becomes a raw material in the next crop cycle.…”
Section: Introductionmentioning
confidence: 96%
“…Schiemenz and Eichler-Löbermann (2010) and Schiemenz et al (2011) have revealed different structures of ash which depend on the plant species burnt, while Park et al (2005) have shown that the composition of ash from wood was not consistent during three years of research. It is assumed that the use of ash from burnt biomass is more satisfactory than the use of sewage sludge, which may contain not only nutrients important for growth but also toxic substances which must be removed before its use in plant cultivation (Fang et al, 2017;Pszczółkowska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, information concerning the use of plant biomass ash as an alternative to artificial fertilizers, which is the key to decreasing agro environment pollution, is difficult to find in the literature. The possibility of decreasing chemical fertilization through the foliar application of microalgae was demonstrated by Pszczółkowska et al (2019), Dębowski et al (2018) and Grzesik et al (2017a). To the best of our knowledge, a study concerning the use of ash from burnt Jerusalem artichoke in sorghum crops, separately or combined with waste from biogas plant and biopreparations, as well as their impact on plants and soil properties under the conditions of limited artificial fertilization has not been performed to date.…”
Section: Introductionmentioning
confidence: 99%
“…Stress caused by salinity of the environment limits the growth and development of terrestrial plants and degrades freshwater flora 26 . In plant cells, osmotic stress induced by NaCl is responsible for the formation of reactive oxygen species (ROS), the resulting oxidative stress leads to degradation of many cellular macromolecules 27 , 28 . However, sodium chloride is the simplest and cheapest stress factor to be used for the effective production of biomass and biofuels on an industrial scale 29 .…”
Section: Introductionmentioning
confidence: 99%